O discurso da revista o cruzeiro e o golpe de 1964 - Carvalho, Helionardo Oliveira de (2018)
Based on the theoretical perspective of the Discourse Analysis of pecheutian strand and supported in the historical studies on the military dictatorship, the present work has the objective to analyze the discourses that make reference to the necessity of a military intervention in Brazil, produced by the magazine O Cruzeiro. It is necessary to reflect on the ways in which the magazine discursivized in its publications this theme and the ideological positions that led to the production of such discourses. The collected discursive sequences were analyzed based on the theoretical assumptions of Discourse Analysis, such as the conditions of production, ideological formation and discursive formation, interdiscourse and imaginary formations, linking the principles of these categories of AD with reflections on the functioning of the discourse of the media. The corpus of analysis of this work consists of statements that were extracted from eight weekly editions of O Cruzeiro, dating from the period of March to April in 1964. The results indicate that the discourses present in the stories and reports that deal with the subjects related to the country’s political scene in that year advocated a military takeover, both to prevent the establishment of a dictatorial regime based on the communist ideas, and to remove the country from the political and economic chaos that, according to the sequences analyzed, were caused by the political actions of President João Goulart